Contrasting pathways to tree longevity in gymnosperms and angiosperms - Brienen, Roel J. W.; Locosselli, Giuliano Maselli; Krottenthaler, Stefan; Gloor, Emanuel; Wrigley, Robyn; Voelker, Steven L.; Altman, Jan; Altmanova, Nela; Anderegg, Leander D. L.; Baliva, Michele; Barua, Deepak; Bazant, Vaclav; et al. (Springer Nature, 2026)
Tree longevity is thought to increase in growth-limiting, adverse environments, but a quantitative assessment of drivers of global variation in tree longevity is lacking. We assemble a global database of maximum longevity for 739 tree species and analyse associations between longevity and climate, soil, and species’ functional traits. Our results show two primary pathways towards long lifespans. The first is slow growth in resource-limited environments, consistent with the “adversity begets longevity” paradigm. The second pathway is through relief from abiotic constraints in productive environments. Despite notable exceptions, long-lived gymnosperms tend to follow the first path through slow growth in cold environments, whereas long-lived angiosperms tend to follow the second (“productivity”) path reaching maximum longevity generally in humid environments. For angiosperms, we identify two mechanisms for increased longevity under humid conditions. First, higher water availability increases species’ maximum tree height which is associated with greater longevities. Secondly, greater water availability increases stand density and inter-tree competition, limiting growth which may increase tree lifespan. The documented differences between gymnosperm and angiosperm longevity are likely rooted in intrinsic differences in hydraulic architecture that provide fitness advantages for gymnosperms under high abiotic stress, and for angiosperms under increased productivity or competition.
Keywords: trees; old growth forests; longevity; dendrochronology